2014
DOI: 10.1044/2014_ajslp-13-0144
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple Measures to Document Change in English Vowels Produced by Japanese, Korean, and Spanish Speakers: The Case for Goodness and Intelligibility

Abstract: English vowels differ with respect to the importance of goodness for accurate identification by listeners. As such, clinicians should examine both goodness and intelligibility when measuring change following pronunciation training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The AVQI, for example, is an acoustic method specifically developed to quantify the level of overall dysphonia in both continuous speech and sustained vowel. Although its validity already has been substantiated in Dutch, German, English, and French across multiple studies with various data acquisition systems, 8,[13][14][15][16][17] its value as a clinical marker of dysphonia severity in other than these western European languages (with differing intonation and timing patterns, voiced-unvoiced sound structures, and vowel types 19,20 ), such as Korean, was still unclear. Furthermore, in contrast to the association between AVQI and G, the correspondence between AVQI and CAPE-V's OS has not been analyzed before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVQI, for example, is an acoustic method specifically developed to quantify the level of overall dysphonia in both continuous speech and sustained vowel. Although its validity already has been substantiated in Dutch, German, English, and French across multiple studies with various data acquisition systems, 8,[13][14][15][16][17] its value as a clinical marker of dysphonia severity in other than these western European languages (with differing intonation and timing patterns, voiced-unvoiced sound structures, and vowel types 19,20 ), such as Korean, was still unclear. Furthermore, in contrast to the association between AVQI and G, the correspondence between AVQI and CAPE-V's OS has not been analyzed before.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this also pertains to Korean, that is, a language presumed isolate or related to Altaic, 18 19,20 It can thus be concluded that both languages strongly differ on various aspects of articulatory and phonatory physiology. Therefore, the present study addressed the following research questions: (1) How well do G ratings correspond with overall dysphonia severity ratings on hybrid CAPE-V scale, when both talker and rater are native Korean speakers?…”
Section: Introductionmentioning
confidence: 93%
“…In addition, Flege states that experience can alter an adult's phonological system. This experience can come from time spent speaking the foreign language (Flege, 1981;Mack, 2003;Munro & Derwing, 2008;Oh et al, 2011) or from direct phonological instruction (Franklin & Stoel-Gammon, 2014). These last two points are important to consider because pronunciation instruction would be of no value if adult phonological systems were intractable.…”
Section: Implications Of Flege's Slm For Adult Language Learnersmentioning
confidence: 99%
“…ASHA clearly states that foreign accents demonstrate speech differences rather than speech disorders (ASHA, 1997). Regardless of this distinction, the same clinical rigor applied to the treatment of speech disorders should also be applied to accent modification services (Franklin & Stoel-Gammon, 2014;Levy & Crowley, 2012;Muller, Ball, Guendouzi, & Muller, 2000;Sikorski, 2005). This clinical rigor is encapsulated in the framework of evidence-based practice.…”
mentioning
confidence: 99%
“…Comprehensibility is a listener's perception of how challenging it is to comprehend an utterance, and accentedness is defined as a listener's perception of the ELL's speech as different from that of the listener's own language community (Derwing & Munro, 2005). Goodness, on the other hand, is defined as a listener's judgment of an utterance's accuracy compared with the listener's concept of an ideal prototype (Franklin & Stoel-Gammon, 2014). A number of studies have investigated how these measures of speech relate to one another (Behrman & Akhund, 2013;Derwing & Munro, 1997;Franklin & Stoel-Gammon, 2014;Munro & Derwing, 1995b;Trofimovich & Isaacs, 2012).…”
mentioning
confidence: 99%